In science's shadow literary constructions of late Victorian women - Murphy, Patricia, 1951- (University of Missouri Press, 2006)
"Through close analysis of noncanonical Victorian-era literature by Thomas Hardy, Wilkie Collins, Charles Reade, Constance Naden, and Marianne North, Murphy reveals how women were often marginalized, constricted, and defined as intellectually inferior as a result of the interplay of sociohistorical trends driven by scientific curiosity and the 'Woman Question'"--Provided by publisher.